Distribution of Cetaceans in the Canary Islands (Northeast Atlantic Ocean): Implications for the Natura 2000 Network and Future Conservation Measures - Inma Herrera; Inma Herrera; Manuel Carrillo; Marcial Cosme de Esteban; Ricardo Haroun (Frontiers in Marine Science)
The waters of the Canary Islands are considered a hotspot for marine biodiversity, especially regarding cetacean species. Based on this fact, this study pays attention to the spatial distribution pattern of cetacean species and the conservation role of the Natura 2000 Network, a set of Special Areas of Conservation (SACs), which were defined mainly based on data compiled in 1996, under the framework of the European Habitats Directive. In recent years, the declaration of conservation areas for cetaceans between the Tenerife—La Gomera Islands by two global conservation programs, Mission Blue (“Hope Spots”) and Whale Heritage Site (“Whale Sanctuary”) sent clear signals of scientific and social interest to promote better protection of the cetacean species in the Canary Islands. The main aim of the designated SACs is the conservation of its biological and ecological diversity, ensuring the long-term survival of the target species in the waters around islands. In this case, the enactment of the SACs was based only on the sparse data available for the common bottlenose dolphin, Tursiops truncatus. This study shows that the spatial distribution of cetaceans in the Canary archipelago generated from a large database of cetacean sightings, from 2007 to 2018. The results obtained show the main marine areas where the different cetacean species are distributed around the different islands of the archipelago. The spatial distribution maps of the cetacean species, when compared with the existing SACs of the Natura 2000, show the need to extend these SACs into the open sea to include more cetacean species and a larger number of individuals for better conservation of the endangered marine mammals. As a consequence, some suggestions were proposed to improve and update the role of SACs in European Northeast Atlantic waters as a key environmental tool for cetacean conservation. The data supporting the recent declarations of these two new milestones the “Hope Spot” and the “Whale Sanctuary” enhance more keystone information to promote a large marine protected area in the Eastern Atlantic Ocean, such as the “Macaronesian Biodiversity and Ecological Migration Corridor for Cetaceans,” a conservation figure that has been already proposed in the scientific literature as a deserving candidate of governmental regulations and policies by Portugal and Spain; it would also require joint cross-border cooperation efforts for marine spatial planning.